2004
DOI: 10.1007/s00415-004-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon �-1a on serum matrix metalloproteinase?9 (MMP-9) and tissue inhibitor of matrix metalloproteinase (TIMP-1) in relapsing remitting multiple sclerosis patients

Abstract: There is emerging evidence that matrix metalloproteinases (MMPs) might be involved in blood brain barrier (BBB) breakdown in multiple sclerosis. A group of natural tissue inhibitors of metalloproteinases (TIMPS) regulates proteolytic activity to prevent tissue damage. TIMP-1 and MMP-9 are known to be secreted as heterodimers and TIMP-1 preferentially functions to inhibit MMP-9 activity. In this present study, the effects of IFNbeta-1a on serum MMP-9 and TIMP-1 were evaluated longitudinally during a one-year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…MMP release as a consequence of Erk1/2 signaling has recently been demonstrated in several cell types including microvascular endothelial cells and HUVECs [25][26][27][28][29][30][31]. MMP9 activity has been associated with increased BBB permeability in models of stroke [33,34] and trauma [35] and its role in immune cell BBB transmigration to the brain is well characterized [36][37][38][39][40]. Macrophages in MS lesions, and in some reports leukocytes, express several MMPs including MMP9 and CSF concentration of MMP9 may reflect disease activity in MS [41].…”
Section: Discussionmentioning
confidence: 99%
“…MMP release as a consequence of Erk1/2 signaling has recently been demonstrated in several cell types including microvascular endothelial cells and HUVECs [25][26][27][28][29][30][31]. MMP9 activity has been associated with increased BBB permeability in models of stroke [33,34] and trauma [35] and its role in immune cell BBB transmigration to the brain is well characterized [36][37][38][39][40]. Macrophages in MS lesions, and in some reports leukocytes, express several MMPs including MMP9 and CSF concentration of MMP9 may reflect disease activity in MS [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the serum MMP-9:TIMP-1 ratio was a good predictor of the number of gadolinium-enhancing lesions [53]. In yet another study, Karabudak et al [54] reported that while MMP-9 levels did not change during a 1 year period with interferon-beta therapy, levels of TIMP-1 increased.…”
Section: Mmpmentioning
confidence: 96%
“…It was demonstrated that matrix metalloproteinase type 9 (MMP-9) activity can be decreased by IFNβ-1b treatment in vitro 16 , which could difficult the migration of lymphocytes across the fibronectin of cerebral endothelium. Another study did not find any difference in the MMP-9 levels during the treatment with IFNβ 17 . Besides the role of the metalloproteinases, IFNβ can modulate the expression and traffic of other molecules like cytokines, chemokines, adhesion molecules and integrins [16][17][18] , improving endothelial barrier function and prevent the transmigration of leukocytes and other neurotoxic mediators across the BBB to sites of CNS inflammation 10 .…”
Section: Effects On Bbbmentioning
confidence: 99%